Frequency of Hyperuricemia in Hypertensive Patients: A Descriptive Cross-Sectional Study at Karachi (Medical Forum Monthly, 2023)
Objective: To find out the frequency of hyperuricemia in patients with hypertension.Study Design: A Descriptive Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the National Institute of Cardiovascular Diseases (NICVD), Karachi from 04-February 2022 to 04-November 2022.Materials and Methods: Demographic profiles of the patients, like gender and age (years), weight (kg), height (cm), and BMI (kg/m2), were recorded. The total sample size was 191 patients. Patients with a prior history of hypertension and who have been prescribed antihypertensive medication for at least six months were classified as hypertensive. Patients with fasting serum uric acid levels≥ 7.0 mg/dL were classified as suffering from hyperuricemia.Results: The mean age was 52.86 ±11.4 years. Mean BMI was 28.93 (±6.8). There were a total of 191 patients. There were 117 (62%) males and 74 (38%) females. Male participants were more than females in this study. In this study 41 (21.47%) were smokers. Most of the participants ( in this study had body mass index (BMI) of < 27.5 kg/m2 while 19.9% had BMI> 27.5 kg/m2. Diabetes was present in 44.7% (71) of the patients. In hypertensive patients, the total prevalence of hyperuricemia was 70(36.5%). Hyperuricemia was more common in diabetic patients (75.7%) compared to non-diabetics (24.3%).Similarly elderly patients (age>50years),active smokers and patients with sedentary lifestyle had higher frequency of hyperuricemia compared to younger patients (age<50 years),non-smokers and patients with active lifestyle and the difference between these groups was statistically significant.Conclusion: Hyperuricemia is a common metabolic condition and is present frequently in patients with hypertension. In our study its prevalence was 36.5%.Hyperuricemia was more common in smokers, diabetics, and elderly patients (age>50 years)